An elegant defense : the extraordinary new science of the immune system : a tale in four lives - Richtel, Matt (New York, NY : William Morrow, an imprint of HarperCollins Publishers, 2019)
"A groundbreaking narrative exploration of the human immune system--the key to human health and longevity--from the Pulitzer Prize-winning New York Times journalist and acclaimed author of A Deadly Wandering"--
Includes index.
Keywords: Immune system -- Popular works; Immunology -- Popular works; Immunologic diseases -- Patients